Tensile properties of ASTM A131 EH36 shipbuilding steel processed by selective laser melting - Wu, Wenjin (2018)
ASTM A131 EH36 shipbuilding steel is a high tensile strength steel used in various shipbuilding applications. Specific low volume high mix applications of EH36 components are commonly required for new-builds and repair vessels. Manufacturing technologies suitable for high mix low volume applications, such as 3D printing, can help solve many production related woes. This study reports on the tensile properties of ASTM A131 EH36 shipbuilding steel processed by selective laser melting. Tensile test coupons were fabricated and tested to ASTM standards.